A Conceptual Study on Banking Frauds in India - Kumar, Dr. Vikram (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Financial institutions are playing vital role for the development of Indian economy, particularly banks. Banks are those financial institutions those are registered under banking regulation Act 1949 to render various financial services to its customers such as receiving of savings and paying it on customers demand. In this ways banks acted as an intermediary in channelization of saving of the nation for the industrial purposes. Frauds means dishonest act or behaviour through which one person gains an advantage over another which results in the loss of the victim directly or indirectly. Now a day’s frauds relating to banks are playing game in the dream of the public. Rs. 9000 Crores fraud and money laundering case by Vijay Malya, business tycoon of India and the Diamond star Nirav Modi’s Punjab National Bank scam of Rs. 13,000 Crores encourages us to understand the concept of banking frauds and its impact on Indian economy. Banks are performing its activities with public savings. Offences relating to banking activities are not confined to banks but have a harmful impact on their customers and society at large. The data used for the study purpose are collected from secondary sources such as from published journals, bulletins and working papers on banking frauds by different authors. In conclude some recommendations have been made to minimize the banking frauds in future course of action in commercial banks providing services in India. Keywords: Banking, Frauds, Assets and Indian Economy.